Targeting Human Long Noncoding Transcripts by Endoribonuclease-Prepared siRNAs. (September 2015) - Theis, Mirko; Paszkowski-Rogacz, Maciej; Weisswange, Ina; Chakraborty, Debojyoti; Buchholz, Frank
Broad sequencing enterprises such as the FANTOM or ENCODE projects have substantially extended our knowledge of the human transcriptome. They have revealed that a large portion of genomic DNA is actively transcribed and have identified a plethora of novel transcripts. Many newly identified transcripts belong to the class of long noncoding RNAs (lncRNAs), which range from a few hundred bases to multiple kilobases in length and harbor no protein-coding potential. Although the biological activity of some lncRNAs is understood, the functions of most lncRNAs remain elusive. Tools that allow rapid and cost-effective access to functional data of lncRNAs are therefore essential. Here, we describe the construction and validation of an endoribonuclease-prepared siRNA (esiRNA) library designed to target 1779 individual human lncRNAs by RNA interference. We present a compendium of lncRNA expression data for 11 human cancer cell lines. Furthermore, we show that the resource is suitable for combined knockdown and localization analysis. We discuss challenges in sequence annotation of lncRNAs with respect to their often low and cell type–specific expression and specify esiRNAs that are suitable for targeting lncRNAs in commonly used human cell lines.